A PEDAGOGIA FROEBELIANA E A EDUCAÇÃO INFANTIL: PERMANÊNCIA E MUDANÇA - Josiele Aparecida Lopes; Nájela Tavares Ujiie (Universidade do Oeste Paulista, 2014)
The present article considers to trace a comparative panorama between Froebel's Pedagogical and the conceptions of Infantile Education in the present time, allowing to develop changes and methodological permanencies and theoretical changes influenced by it in our institutions. This way we use a theorerical research of a bibliographical matrix, based on authors like Angotti (1992), Arce (2002, 2004); Kuhlmann Jr (2007), Kishimoto e Pinazza (2007), among others that sought to clarify the froebelianas conceptions, the context of its life and work, beyond approches of its theory with the present time of Infantile Education, understanding this analytical process of this classic of the education of children, as of utmost importance for the improvement of the quality of infantile education and the research on the topic. While conclusive aspects we understand the contributions of Froebel's Pedagogical towards the treatment of childhood today, as well as the critics directed to its theory/methodology and we ponder that it is important to analyze the past critically in a way to notice the permanencies and changes, which makes us understand the present, seeking to plan and replan the future.